Molecular Characterization and Clinical Relevance of N6-Methyladenosine Regulators in Metastatic Prostate Cancer - Liu, Qiwei; Li, Zhen; He, Lizhao; Li, Ke; Hu, Chen; Chen, Jialiang; Zhou, Fangjian; Wang, Jun; Li, Yonghong; Xiao, Hengjun (Frontiers in Oncology, 2022)
Background Prostate cancer is a leading malignancy in the male population globally. N6-methylation of adenosine (m6A) is the most prevalent mRNA modification and plays an essential role in various biological processes in vivo. However, the exact functions of m6A in metastatic prostate cancer are largely unknown. Here, we aimed to investigate the relative role of m6A regulators in metastatic prostate cancer. Methods This study used RNA-seq and clinical data of metastatic prostate cancer to elucidate the association between N6 methylation and metastatic prostate cancer. And transwell, wound healing and CCK-8 assays were performed to confirm our informative outcomes. Results Based on 21 m6A regulators associated with prognosis, two molecular subtypes of metastatic prostate cancer were identified. Surprisingly, we observed that each subtype had unique prognostic characteristics. We then identified two subtypes of tumours based on 2330 m6A phenotype-associated genes, and one subtype was related to dismal prognosis. Finally, based on m6A-associated genes, we constructed a prognostic model to predict the outcomes of patients with metastatic prostate cancer. We found that this prognostic model was significantly correlated with biological functions such as DNA repair and mismatch repair, and patients with high m6A scores may be appropriate candidates for pharmacy therapy targeted for DNA repair, such as PARPi. Conclusions This work illustrated the nonnegligible role of m6A modification in the prognosis of metastatic prostate cancer. Evaluating the m6A risk scores of individual tumours will guide more effective judgement of prognosis as well as treatments for metastatic prostate cancer in clinical practice.